Comprehensive Analysis of Oral Health-Related Quality of Life (OHRQoL) in Periodontitis Patients: Evaluating the Impact of Non-Surgical and Surgical Periodontal Therapy - Ratnawati, Irma Dewi; Rizky, Novi Sagita; Styaningrum, Yunita; Rahman, Erwid Fatchur; Aditya, Grahita; Putri, Nabella Devyanna; Pratiwi, Rosa (Jurnal Medali, 2025)
Introduction: Periodontitis is a chronic inflammatory condition that affects the supporting structures of the teeth. Due to its often asymptomatic progression in early stages, timely diagnosis is frequently challenging.Objective: This study aimed to assess the impact of non-surgical and surgical periodontal treatments on the Oral Health-Related Quality of Life (OHRQoL) among individuals diagnosed with periodontitis.Methods: An observational analytic study with a cross-sectional design was conducted using a pre-test and post-test group approach. The study involved 100 patients aged 18–60 years who met predefined inclusion and exclusion criteria and underwent periodontal therapy either non-surgical or surgical at Sultan Agung Islamic Dental and Oral Hospital (RSIGM) between August and December 2024. The OHIP-14sp questionnaire was used to measure OHRQoL across seven domains using a Likert scale. Data were analyzed using descriptive statistics and paired t-tests to evaluate differences between pre- and post-treatment scores.Results: A marked reduction in OHIP-14sp scores was observed across all domains following treatment. The most pronounced improvements occurred in the domains of social disability (−46.2%) and functional limitation (−45.1%). Overall, the total OHIP-14sp score improved by 43.9%. All domains exhibited statistically significant differences between baseline and follow-up scores (p < 0.001). Conclusion: The findings indicated that both non-surgical and surgical periodontal therapies contributed significantly to enhancing patients’ quality of life by alleviating physical discomfort and improving psychological and social well-being.